CHARACTERIZATION OF BIOFILM FORMING ABILITY OF PROBIOTIC CANDIDATES ISOLATED FROM STOOL SAMPLE OF STUNTED AND NORMAL INFANTS - Nabila Tores, Farah
Stunting is a condition of impaired growth in toddlers due to chronic malnutrition, particularly during the first 1,000 days of life. According to the 2022 Indonesia Nutrition Status Survey (SSGI), the national stunting prevalence was 21.6%, with West Java Province reporting a prevalence of 20.2%. Probiotics, a group of microorganisms, can regulate gut microbiota, prevent intestinal diseases, enhance the immune system, produce bacteriocins, exhibit antioxidant activity, and produce extracellular enzymes, thus having potential in stunting prevention. This study aims to: (1) Determine the abundance and diversity of culturable microbes in fecal samples from stunted and normal infants, (2) Assess the biofilm formation ability of probiotic candidate microbes from fecal samples under low pH stress (3, 4, 5), (3) Evaluate the biofilm formation ability of probiotic candidate microbes from fecal samples under 0.3% (w/v) bile salt stress, and (4) Determine the growth patterns of selected probiotic candidates. The study utilized fecal samples from stunted and normal infants under 12 months old. The research employed general media (Luria Bertani) and selective media (Pantothenate Lactobacillus Agar; deMan, Rogosa, Sharpe Lactobacillus Agar; Glucose Yeast Extract Agar) incubated at 37°C for 48 hours. Probiotic isolate selection was conducted under low pH stress (pH 3, 4, 5) and 0.3% (w/v) bile salt stress. Biofilm analysis was performed using a biofilm assay in Luria Bertani medium with varying pH and 0.3% (w/v) bile salt stress, incubated without agitation at 37°C for 48 hours. The growth patterns of selected probiotic candidates were observed through growth curves over 24 hours in Luria Bertani medium at room temperature without agitation. Isolation from the four growth media revealed higher bacterial abundance in stunted samples (3.34x109 CFU/g) compared to normal samples (2.13x109 CFU/g). Twenty-one isolates with white, circular colonies and entire margins, predominantly Gram-negative bacilli, were obtained. Seven isolates (FS403, FS404, FS304, FS305, FS306, FS501, FN304) were identified as Moderate Biofilm Formers (MBF) based on survivability and biofilm formation in media with low pH (3, 4, 5, 7) using an OD Cut-off of 0.239. Five isolates (FS403, FS404, FS304, FS306, FS501) maintained MBF capability under low pH (4, 5) and 0.3% (w/v) bile salt stress with an OD Cut-off of 0.548. Growth curves indicated that isolates FS403 and FS404 had a log phase during the first 12 hours with growth rates of 0.60/hour and 0.76/hour, respectively, while isolates FS304, FS406, and FS501 had a log phase during the first 9 hours with growth rates of 0.75/hour, 0.82/hour, and 0.72/hour, respectively.